STUDY OF BIOLOGICAL ASPECTS AND MANAGEMENT OF TUNA AND SKIPJACK TUNA THAT LANDED IN THE FISHING PORT OF WEST SUMATRA - Yusrizal, Yusrizal; Nurlaela, Eli; Nugraha, Erick; Kusmedy, Bongbongan; Dewi, Priyantini; Saputra, Aman; Setiawan, Hari; Suharti, Ratna; Maulita, Mira; Rachmad, Basuki; Choerudin, Hery; Muallim, Rahmat; Husen, Eddy Sugriwa; Syamsuddin, Syarif (Jakarta Technical University of Fisheries, 2022)
Tuna and skipjack are large pelagic fish that have high economic value and have a very wide export market. The need for and the high market demand for tuna and skipjack causes the intensity of catching this fish to increase. To ensure that the potential of these fish resources remains sustainable, it is necessary to properly manage fisheries.The purpose of this study was to examine several aspects of biology, aspects of capture fisheries, aspects of utilization and management of yellow fin tuna and skipjack tuna. Data collection for yellowfin tuna was focused on one location, namely PPS Bungus, while data collection for skipjack tuna was focused on 4 location points, namely PPS Bungus, PPP Carocok Terusan, PPI Kambang and PPI Tiku. Productivity and cultivation levels of yellowfin tuna in West Sumatra have tended to decline in the past 4 years (2017-2020). Skipjack tuna in the West Sumatra region caught by boat charters was indicated to be overfishing, while skipjack tuna caught by troll showed the fish caught had not spawned yet. The productivity of skipjack tuna has fluctuated over the past 5 years (2016-2020).